2018
DOI: 10.1024/0300-9831/a000571
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pro-inflammatory Dietary Intake and Non-Alcoholic Fatty Liver Disease: Findings from Iranian case-control study

Abstract: Abstract. Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is considered as a major health problem in the world. There is much evidence that diet and dietary factors play an important role in inflammation, and consequently pathogenesis of NAFLD. To investigate the role of diet in the development of inflammation, we can use the Dietary Inflammatory Index (DII), which has been shown to be predictive of levels of inflammatory markers. Methods: 295 incident cases were selected using the convenience-sampling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
5
14
1
Order By: Relevance
“…In terms of markers of liver function, positive associations between the AE-DII, GGT, ALT and AST were observed. As opposed to prior observations (49,50) , the AE-DII was not associated with increased GGT, AST and ALT levels in the PURE-NWP-SA population through the pathway of obesity/fatty liver disease, as the associations remained after adjustment. Instead the associations appear, at least in part, to be related to alcohol consumption, as adjustment therefore nullified the association between the AE-DII and the liver enzymes.…”
Section: Ae-dii In the Pure-nwp-sa Cohort: The Role Of Urbanicitycontrasting
confidence: 99%
“…In terms of markers of liver function, positive associations between the AE-DII, GGT, ALT and AST were observed. As opposed to prior observations (49,50) , the AE-DII was not associated with increased GGT, AST and ALT levels in the PURE-NWP-SA population through the pathway of obesity/fatty liver disease, as the associations remained after adjustment. Instead the associations appear, at least in part, to be related to alcohol consumption, as adjustment therefore nullified the association between the AE-DII and the liver enzymes.…”
Section: Ae-dii In the Pure-nwp-sa Cohort: The Role Of Urbanicitycontrasting
confidence: 99%
“…In summary a positive association was observed between the DII and endometriosis in this case–control study. One of the possible mechanisms for the positive association between DII and the risk of the endometriosis and other chronic inflammatory states might be through the effect of a pro-inflammatory diet, which is known to increase inflammatory cytokines (IL-1, IL-6, and TNF-α) 39 ; to impair antioxidative cell defense system; and to encourage NF-ΚB dependent pathway. 40 This study adds to evidence suggesting that diet-associated inflammation is involved in the pathophysiology of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Individual Intake − Mean SD Table 1 shows the distribution of 82 cases of GC and 95 controls according to the selected variable [7,8]. The mean age was 48.33 ± 10.74 and 51.36 ± 11.81 in the case and the control groups, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Given that the therapies for GC are limited, and the survival chance is low, prevention can be a very effective strategy to reduce the mortality from GC [4][5][6]. Several studies have found a link between the incidence of GC and unhealthy diets [7,8]. In addition, the association between dietary antioxidants and the reduction of the incidence and prevalence of GC has been observed [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation